The Toa Dilemma: Responses to the Public Use of Loudspeakers in Indonesian Local Tradition - Kango, Andries; Abdullah, Selfia; Thahir, Muhammad; Fata, Ahmad Khoirul; Kamaruzzaman, Kartini (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This study explores community responses to the use of loudspeakers during the Dikili tradition in Tomulabutao, Gorontalo, Indonesia. Dikili, an overnight religious ritual, often features amplified chants and hymns as part of the local soundscape and cultural identity. While these sounds are familiar and accepted by indigenous Gorontalo residents, they have sparked varied responses from non-local newcomers living in mixed housing areas. Using a qualitative approach, the study draws on in-depth interviews with residents to gain an understanding of their perceptions of religious sound in shared spaces. Findings reveal that while many non-Gorontalo residents gradually acclimate to the broadcasts, concerns persist regarding excessive volume. In response, mosque management implemented volume adjustments to strike a balance between cultural expression and residential comfort. The study emphasizes the importance of dialogue and negotiated practices in fostering social harmony within diverse, multicultural communities.